Dinamika Sistem Kesejahteraan dan Modal Sosial di Masyarakat Banjar Pakraman-Bali - I Ketut Meniarta; Wawan Mas'udi; AAGN Ari Dwipayana (Jurnal Ilmu Sosial dan Ilmu Politik, 2009)
This study explores and uncovers the welfare system of Banjar Pakraman-Bali community existing nowadays, and then the history and development are observed. Besides that, there is also observation on state welfare systems and the market worked in Banjar Pakraman community and its interaction. Due to welfare is a complex matter, then this study only focused on the fulfillment of public main necessaries in order to specify the discussion.The result suggests that community of Banjar Pakraman Batannyuh has a welfare system which was practiced since long time ago. This system is based on Menyama Braya and Suka Duka values, its institutions form of Keliran, Dadia and Sekehe besides through mechanisms of mutual cooperation, arisan, contribution and giving each other. The main principle of this system is even redistribution and balance without differentiating economic status of community, thus it is not pro poor. When public condition is homogenous, this system is effective to bring public welfare into reality. Whereas, with the heterogeneity in community and high discrepancy due to market system inducing makes this system become not effective. Even this system burdens public.On the other hand, state welfare system also reaches the community life of Banjar Pakraman. This system which derived from state is not replacing welfare system of Banjar Pakraman, but there is a variation on relation patterns, it is depend on the policy. In general, subsidy policy for poor community is ineffective, thus people makes an even redistribution according to main principle of Banjar Pakraman welfare system.The dynamics of public welfare system in Banjar Pakraman is phenomenon of social changing. This dynamics occurs due to influence from state and free market which got response from Banjar Pakraman community, thus the free market become more dominant. The influence of free market had change public behaviors, thus improve the efficiency and effectiveness of custom activity.